Development and Characterization of Thermal Insulation Geopolymer Foams Based on Fly Ash - Łach, Michał; Mikuła, Janusz; Lin, Wei-Ting; Patrycja Bazan; Beata Figiela; Korniejenko, Kinga (Proceedings of Engineering and Technology Innovation, 2020)
The main purpose of the article is to present the differences in the parameters of geopolymer foams obtained in the same way, which is associated with difficulties in controlling the foaming process. Difficulties in controlling the foaming process of geopolymers are the direct reason for the lack of implementation of such materials nowadays. The article shows the results for experimental research, especially research into insulation, physical, and mechanical properties for the designated foamed materials. Microspheres (75%), sand (5%) and fly ash (20%) were used to produce foamed geopolymers. Hydrogen peroxide was the foaming agent. Heat conduction coefficients of 0.08-0.07 W/mK were obtained. The material density was obtained at the level of 363-375 [kg/m3] and the compressive strength was 520-683 [kPa]. The results showed that geopolymers can be a good alternative to conventional insulation materials, but the foaming technology should be developed so that it is stable and allows for reproducible material parameters.